From an innovative space to a traditional place: Palacio Bar an actor and a spectator of Curitiba's urban dynamics (1930-2006) (Tempo e Argumento, 2011)
Palacio Bar, established in Curitiba in the 1930s, remains known by its traditional features. This article explorespress sources that advocate the traditional character of Palacio Bar before the sweeping changes that occurred around them (in addition to some internal changes). Thus, the relative immutability of Palacio in relation to the urban transformation of Curitiba during the twentieth century, emphasizes the place as a space of remembrance. The nostalgia emerges in this context, as a consequence of feelings aroused by some unique elements of thePalacio, as the menu and the environment.
Keywords: traditional restaurant; urban dynamics; sensitive heritage